BIOLOGICAL ASPECTS OF THE RED MEAL OF THE FLOURS Tribolium castaneum (Herbst) - LÓPEZ-AVILA, ARISTÓBULO (Revista Colombiana de Entomología, 1985)
Under rearing conditions of the entomological laboratory (21°C and 65-70°/o RH) of 1CA’s experimental center "Tibaitatá" the life cycle of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) was determined. The life span from the egg, to adult was 82.44 days and the adult longevity was over five months. The major mortality (52.45%) was observed during the larval stage. A short description of each stage is made, and while evaluating the damage the insect could cause to stored wheat grains it was concluded that T. castaneum cannot be considered a primary pest in this cereal.